Effect of native mycorrhizal and phosphorus in corn yields in Guárico, Venezuela - Eliecer M. Cabrales H; Marcia Toro; Danilo Lopez-Hernández (Temas Agrarios, 2016)
This study evaluated the efficiency of 4 native species of fungi mycorrhizal and mixing Scutellospora pellucida, Scutellospora calospora, Glomus leptotichum and Acaulospora mellea in absortion N and P and its effect on crop yields of hybrid corn HIMECA 3005 with 4 doses of P (0, 27, 54 and 80 kg ha-1 of P2O5). The study took place in soils of sabanna of Guarico state – Venezuela. Fungi were seeded at 0,9 between rows and 0,4 m between plants, sampling was done in the opposite leaf the corn cob in flowering stage. Quantification of P and N leaf was made by Murphy - Riley and distillation Kjeldalh respectively, whereas yields were evaluated in the three central rows of each plot. A randomized block design with factorial arrangement was used, the ANAVA, It was performed with Statistic 8.0. Findings revealed that doses of P and evaluated morphotypes influenced the decision-N and P in the corn plant, 54 kg ha-1 of P2O5 and consortium of inoculants those of better efficiency for the taking of N; while the dose of 54 kg ha-1 de P2O5 and Scutellospora pellucida formaking of P. It was concluded that these two inoculants can decrease the dose of P to 25% and increase maize yields by up to 100% based on the production of the area (2000 kg ha-1 ).